Market responses on integrated reporting: Does corporate reputation matter? - Juniarti; Halim, Cynthia; Wehantouw, Evelyn (International Journal of Management and Sustainability, 2025)
This study investigates the market response to the adoption of Integrated Reporting (IR) among companies listed on the Indonesia Stock Exchange and examines whether corporate reputation moderates this relationship. A quantitative approach was used, applying descriptive analysis and hypothesis testing with the Common Effect model. The analysis compared IR adopters and non-adopters using Cumulative Abnormal Return (CAR) as a measure of market response, both before and after the COVID-19 pandemic. Integrated Reporting (IR) adopters had greater Cumulative Abnormal Return (CAR) values than non-adopters, indicating stronger market responses. This impact persisted before and after COVID-19. Further descriptive analysis showed no significant differences in company reputation, firm size, and leverage between IR adopters and non-adopters. Additionally, corporate reputation did not significantly moderate the relationship between IR adoption and market response. IR adoption positively influences market perception, supporting signaling theory. The market rewards transparent and comprehensive reporting, regardless of prior corporate reputation. IR can be an effective tool for companies seeking better market valuation. Investors should consider IR adoption in their decision-making, and policymakers are encouraged to promote IR to enhance market transparency and efficiency.